Analyzing the Factors Affecting Sales Opportunities for Processed Meat Packaging in Thailand - Sarunpong Akkaratananpong; Thanate Piromgarn; Sirisyos Kijmongkolvanich; Songwut Egwutvongsa (Revista de Gestão Social e Ambiental, 2024)
Objective: The objective of this study is to analyze the retail market potential of processed meat products in Thailand and establish a structural equation model. Entrepreneurial SMEs registered commercially in Thailand. Theoretical Framework: This research applies a packaging design concept that can meet the needs of modern consumers. The new packaging must have the following characteristics: 1)It must create a positive feeling while consumers use it. 2) Must have low production costs. 3)Must be able to arouse consumer interest. 4)has a beautiful layout Method: This research is applied research consisting of 5 steps: 1) Data collection step. 2) Design process 3)Trial use process 4) Evaluation process 5) Steps for analyzing and presenting factors that affect. This research uses the following statistics: 1) Mean 2) Standard Deviation: SD 3) Exploratory Factor Analysis: EFA 4) Confirmatory Factor Analysis: CFA 5) Multiple Regression. This research analyzed data using the SPSS program and the Amos program. Results and Discussion: The results of this research show the importance of 4 factors that influence the increase in consumer satisfaction: Factor 1 design guidelines, Factor 2 access to products, Factor 3 identity, Factor 4 understanding of the future of the retail market with the likely direction of the market. All four factors are important to the opportunity to sell processed meat products in the Thai retail market. Research Implications: The research results reveal the influence of 4 factors that together influence the level of consumer satisfaction. By knowing the interrelationship of these 4 factors, which is considered a fact arising from this research. Therefore, small entrepreneurs in Thailand can apply all four factors to designing their own processed meat packaging. And there is an opportunity to increase the sales volume even more in the future. Originality/Value: The results of this research contribute to knowing the factors that influence the level of consumer satisfaction with processed meat products available in the retail market of Thailand. This fact helps reduce the inequality in competition between small and large operators in the processed meat retail market of Thailand. Therefore, it is an important part that helps increase the competitive potential of small entrepreneurs in the future.
Keywords: Consumer Packaging Perceptions and Trends